Congenital Vaginal Agenesis, Davydov Procedure - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Congenital vaginal agenesis, also called Müllerian agenesis or Rokitansky–Mayer–Küster–Hauser syndrome, is a rare anomaly of the female genital tract. The affected individuals present with primary amenorrhea, varying degree of uterovaginal anomalies, infertility, and other associated renal, spine, and skeletal malformations. Embryologically, the vagina is formed from the fusion of the two embryonic structures: the upper part from the Müllerian duct system and the lower third from the urogenital sinus. Müllerian agenesis is caused by embryologic underdevelopment of the Müllerian duct, with resultant agenesis or atresia of the vagina, uterus, or both. We report the case of a 25-year-old woman who presented with complaints of delayed onset of menses and inability to have sexual intercourse with her partner. She had well-developed secondary sexual characteristics. She had never experienced penetrative sexual intercourse despite being married for 2 years. A general physical examination revealed a young woman of normal stature. She had well-developed breast (Tanner stage 5). The clitoris and pudendal cleft were normal. There was normal external urethral meatus with blind ended vagina of 2 cm long. A digital rectal examination revealed good sphincteric tone with no uterus or cervix palpated. A diagnosis of congenital uterovaginal anomaly was made. A buccal smear done revealed XX karyotype. She was counseled about her condition. Consents for surgery and media release were sought and obtained. A Davydov procedure for neovaginal construction was made and her postoperative condition was satisfactory. Congenital vaginal agenesis is a rare condition with profound effects on the affected individuals. Therefore, proper counseling on future fertility options and the need for neovaginal construction for improved sexual satisfaction should never be overemphasized among others.